The Junior Classics, Volume 6: Old-Fashioned Tales - Patten, William, 1868-1936 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Junior Classics, Volume 6: Old-Fashioned Tales" by William Patten is a collection of classic stories likely compiled in the early 20th century. This volume features enchanting narratives such as "The Race for the Silver Skates" and "Nelly's Hospital," presenting charming tales that resonate with the moral values and themes of kindness, adventure, and youth. Through various tales, the collection celebrates the spirit of imagination in childhood and the importance of life lessons taught through both fantastical and relatable characters. The opening portion of the text begins with "The Race for the Silver Skates" by Mary Mapes Dodge, immersing readers in a picturesque winter scene where a skating competition unites townsfolk in excitement. Various characters, including peasant boys and girls, prepare for the race on a frozen lake near Amsterdam. These skaters are vividly described in their festive attire, embodying the lively atmosphere of the event. Notably, the protagonist, a spirited young girl named Gretel, and her brother Peter, are introduced, setting the stage for themes of competition, community spirit, and the joy of youth as they eagerly compete for the coveted silver skates. This opening successfully captures the reader's interest by blending colorful imagery with a sense of anticipation for the ensuing race. (This is an automatically generated summary.)
The Race for the Silver Skates / Mary Mapes Dodge -- Nelly's Hospital / Louisa M. Alcott -- A Fox and a Raven / Rebecca H. Davis -- The Private Theatricals / Mrs. A. D. T. Whitney -- A Case of Coincidence / Rose Terry Cooke -- The Flight of the Dolls / Lucretia P. Hale -- Solomon John Goes for Apples / Lucretia P. Hale -- Wild Robin / Sophie May -- Deacon Thomas Wales' Will / Mary E. W. Freeman -- Dill / Mary E. W. Freeman -- Brownie and the Cook / Mrs. Dinah M. Craik -- Brownie and the Cherry Tree / Mrs. Dinah M. Craik -- The Ouphe of the Wood / Jean Ingelow -- The Prince's Dream / Jean Ingelow -- A Lost Wand / Jean Ingelow -- Snap-Dragons: A Tale of Christmas Eve / Juliana H. Ewing -- Uncle Jack's Story / Mrs. E. M. Field -- Bryda's Dreadful Scrape / Mrs. E. M. Field -- The Cratchits' Christmas Dinner / Charles Dickens -- Embellishment / Jacob Abbott -- The Great Stone Face / Nathaniel Hawthorne -- The King of the Golden River / John Ruskin -- The Two Gifts / Lillian M. Gask -- The Bar of Gold / Lillian M. Gask -- Uncle David's Nonsensical Story / Catherine Sinclair -- The Grand Feast / Catherine Sinclair -- The Story of Fairyfoot / Frances Browne -- Alice in Wonderland / Lewis Carroll.
Release date is 2004-09-01
Produced by Wendy Crockett, Charles Franks and the Online Distributed Proofreading Team
Keywords: Children's literature